PENGARUHRISK BASED CAPITALTERHADAP PROFITABILITASPERUSAHAANASURANSISYARIAHSTUDY PADAPERUSAHAAN ASURANSI YANG TERDAFTAR DI AASI - Mubarok, Nurul; Rahayu, Dede (I-Economics, 2017)
Risk Based Capital (RBC) is a capital adequacy ratio of the risks covered and became one of the main indicators in assessing the financial health of insurance companies. This study is intended to determine how the influence Risk Based Capital to Profitability in Islamic Insurance company registered in AASI. This study aimed to determine the effect Risk Based Capital to Profitability in Islamic Insurance company registered in AASI. The data used in this research is secondary data such as financial statements of the company Sharia Insurance in Indonesia for the period 2012-2015. Samples were taken using purposive sampling technique. Samples were 12 companies from 45 Islamic insurance company registered in Sharia Insurance Association of Indonesia in 2012-2015. Data analysis technique used is the test panel fixed effect, random effect test and simple linear regression using eviews7. Based on the results of research and discussion expressed Risk Based Capital does not have a significant influence on the profitability ROA and ROE level of influence by 6,513% and 4.519% sedangan rest influenced by other factors. Imlikasi from the research is that the shortcomings in the fulfillment of obligations will mengerus capital of the insurance company that has been provided. However, if the solvency excess will lead idle funds so as not productive and will also remove the opportunity to earn income(profitability).